Balasore papers 1693-1949 - "Chatrath, K. J. S." (Panchkula, 2011)
During the seventeenth century, a number of foreign trading companies, backed by their respective governments, set up small trading posts near sea shore in various part of India. Being next to the sea was logistically important as both the imports from as well as the exports to Europe were through the sea route. Some of these gradually got converted into towns under control of the foreign companies while the others withered away.
Keywords: Balasore-Orissa-India